2016
DOI: 10.23910/ijbsm/2016.7.1.1486
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Coconut Genotypes Against Coconut Eriophyid Mite (Aceria guerreronis Keifer.)

Abstract: The coconut genotypes were screened for their level of susceptibility to coconut eriophyid mite. Based on the mean damage Grade Index score none of the coconut genotypes were found to be resistant to eriophyid mite. However the genotypes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The mite causes scarring in the growing nuts especially 2-3 months before maturation stage since the mite inhabits the basal portion of the nut below the perianth. Eriophyid mite infestation is prevalent in India [80]. Various reports have shown that the Lono cultivar ranges from susceptible [81] to moderately resistant [80] against the eriophyid mite (Aceria guerreronis Keifer), while the cultivar had been also shown to be 71% resistant, and is the second most resistant variety following the Chowghat Green Dwarf, against the root wilt disease [82].…”
Section: Lonomentioning
confidence: 99%
“…The mite causes scarring in the growing nuts especially 2-3 months before maturation stage since the mite inhabits the basal portion of the nut below the perianth. Eriophyid mite infestation is prevalent in India [80]. Various reports have shown that the Lono cultivar ranges from susceptible [81] to moderately resistant [80] against the eriophyid mite (Aceria guerreronis Keifer), while the cultivar had been also shown to be 71% resistant, and is the second most resistant variety following the Chowghat Green Dwarf, against the root wilt disease [82].…”
Section: Lonomentioning
confidence: 99%
“…The coconut mite Aceria guerreronis Keifer (Acari: Eriophyidae) is the most expressive pest to affect coconut plantations in tropical America, Asia, and Africa [12] [13] [14] [15]. A. guerreronis populations are found in restricted spaces under fruit bracts [16] [17].…”
Section: Introductionmentioning
confidence: 99%
“…The attack of this pest leads to premature fruit drop, reduced fruit size, weight and water volume. Aesthetic skin necrosis also reduces the value of fruits intended for the fresh market [12] [19].…”
Section: Introductionmentioning
confidence: 99%